Editorial of the Annals 2022. Important advances in the digitization of the Journal in times of pandemic. Dra. Mercedes Martínez León, Full Member and Librarian of the Royal Academy of Medicine and Surgery of Valladolid. (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
My first objective since I was named Academic Librarian was to carry out the necessary digitization process of our Annals Magazine of the Royal Academy of Medicine and Surgery of Valladolid, which until issue 55 of 2018 was printed on paper. It was an important and complicated task because we had to adapt in times of pandemic to the new times of Information and Communications Technologies. And this was also the only way in which the Anales Magazine could continue to be published, so it represented a great responsibility and effort to be able to carry out this project, especially when the essence of the Royal Academy of Medicine and Surgery has always been power. publish the Anales Magazine with all our scientific works and activities. Furthermore, we had the great advantage that being digital with all publications in open access was a very good opportunity to give greater visibility and dissemination to our scientific work.
Keywords: Editorial; Medicine; Cirugy; Valladolid